STRATEGI KOMUNIKASI DALAM MANAJEMEN PENGEMBANGAN ORGANISASI - Fifi Hasmawati; Aliasan Aliasan (Yonetim Jurnal, 2022)
The development Organization of Islamic boarding institutions as one of religius social organization in Indonesia gets special attention from former religius organizations. This attention is reasonable, because in no longer time Organization has spreaded all over Indonesia / Nusantara. This phenomenon is interesting to study in the perspective of communication science : what is the communication concept and strategy of organization development ? Based on the problem, this reseach is aimed to study and find the communication concept and strategy of development . This reseach uses qualitatif-phenomenology approach, and to collect data is used interview, partisipation observation, and documentation. The reseach subject is the general Organization . The result of reseach shows that there are some proponent / supporting factors in the communication concept and strategy of organization developiment ,its like to (1) becoming the values and concept of religion as guidance to rule all organization activities, (2) using command management approach “imamah jama’ah” as communication strategy of organization development.